Pemberdayaan Masyarakat Melalui Sosialisasi Progam UMKM Dalam Pembuatan Salad Buah Didesa Sanggalima - Muamar Al Qodri; Rayhan Hanafi; M. Hidayat; Amelia (peduli riset dan pengabdian masyarakat, 2025)
Community Empowerment Program through the Socialization of Micro, Small, and Medium Enterprises (MSMEs) in Fruit Salad Production in Sanggalima Village, Gebang District, Langkat Regency. This program aims to enhance the skills and knowledge of the local community in developing independent business opportunities. Organized by KKN 05 students, this socialization initiative serves as an effort to improve the entrepreneurial competencies of residents. Through educational outreach and training in fruit salad production, the program seeks to enable the community to create high-value processed products that contribute to household economic sustainability. The implementation of this program involves educational counseling, practical demonstrations of fruit salad preparation, and fundamental marketing training utilizing social media platforms. The outcomes indicate a notable improvement in the community’s ability to process fruit into nutritious and attractive food products while simultaneously fostering new MSME-based business opportunities within the village. Accordingly, this initiative is expected to serve as a foundational step toward strengthening the economic independence of the Sanggalima Village community.